External validation of the RENAL nephrometry score in renal tumours treated by partial nephrectomy. (12th July 2012) - Long, Jean‐Alexandre; Arnoux, Valentin; Fiard, Gaelle; Autorino, Riccardo; Descotes, Jean‐Luc; Rambeaud, Jean‐Jacques; Boillot, Bernard; Terrier, Nicolas; Arvin‐Berod, Alexis; Moreau‐Gaudry, Alexandre
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Using a standardized classification for renal tumours is a major step towards an objective comparison of the indications and expected outcomes of partial nephrectomy (PN). Several scores have been described, including the RENAL nephrectomy score (RNS), to evaluate the anatomical features of a renal tumour and predict the surgical challenges with particular regard to PN. Previous studies show discrepancies with regard to the effectiveness of using the RNS to predict postoperative outcomes. Although we showed that conversion to radical nephrectomy was predicted by the RNS, the occurence of complications was more difficult to predict. Objective To evaluate the RENAL nephrometry score (RNS) as a predictor of the perioperative outcomes of a partial nephrectomy. Patients and Methods A retrospective review of 177 consecutive patients who were candidates for an open partial nephrectomy (OPN, n = 159) or a laparoscopic partial nephrectomy (LPN, n = 18) from August 2008 to January 2011 was undertaken. Tumour complexity was stratified into three categories: low (4–6), moderate (7–9) and high (10–12) complexity. Complications, and surgical and renal outcomes were recorded and analysed. Predictors of conversion to radical nephrectomy (RN) and complications were assessed using univariate and multivariate logistic regression. Multiple linear regression was used to evaluate the prediction of postoperative estimated glomerular filtration rate (eGFR) and warm ischaemia time (WIT). Results The median RNS was 7 (interquartile range 6–9). Tumour complexity was assessed as low in 72 (40.6%), moderate in 87 (49.2%) and high in 18 patients (10.2%). There were no significant differences among the three groups with respect to demographic characteristics, operating time, estimated blood loss, transfusion, length of stay, complications and positive surgical margins. Conversion to RN occurred in 29 patients (16.3%). RNS was significantly associated with an increased risk of conversion to RN (odds ratio [OR] = 3.5, P = 0.01 and OR = 6.7, P = 0.005, respectively, for moderate vs low, and high vs low complexity groups). On multivariate analysis, RNS was the only independent predictor of WIT (P = 0.03) and conversion to RN (P = 0.008), but failed to predict postoperative eGFR (P = 0.84) and the occurrence of major complications (P = 0.91). Conclusions In the present series, RNS predicted an increased risk of conversion to RN and prolonged WIT. RNS was not a predictor of complications and postoperative renal function.